Elementy rachunku wyników banku - Kopiński, Adam (Elements of the Account of a Bank's Financial Results, 2007)
The paper describes the account of a bank's financial results as a juxtaposition of revenues, costs and financial results presented in the form of a diagram that illustrates different levels of financial result. The objective of the paper's second section is to characterize particular types of a bank's revenues as well as corresponding costs but also different categories of financial results associated with them which are the outcome of a bank's activity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 283-291